Artificial Intelligence: An Analytical Study: Its Impact on Marketing Rate Through Electronic Applications in Saudi Arabia - Sabah Abdellatif Hassan Ahmed (International Journal of Intelligent Systems and Applications in Engineering, 2025)
This study examines the role of artificial intelligence (AI) in shaping e-commerce trends and its impact on consumer behavior in Saudi Arabia. With the increasing integration of AI technologies, such as machine learning algorithms, chatbots, and virtual assistants, e-commerce platforms are experiencing a transformation in customer engagement, sales performance, and personalized shopping experiences. The research utilizes a mixed-methods approach, combining quantitative and qualitative data from a sample of 349 participants across various regions in Saudi Arabia. The findings reveal that AI-driven features significantly influence online shopping behaviors, with users reporting enhanced satisfaction, increased shopping frequency, and improved decision-making processes through personalized recommendations and dynamic pricing. Key insights from the study include gender-based preferences for specific e-commerce platforms and distinct challenges related to AI adoption, such as privacy concerns, mistrust in AI recommendations, and system complexity. The study also highlights the need for e-commerce platforms to address these challenges by enhancing transparency, refining AI-driven tools, and ensuring a balance between personalization and consumer privacy. Despite these challenges, the data suggest optimism regarding AI’s potential to further transform the e-commerce landscape in Saudi Arabia, offering valuable opportunities for businesses to improve customer experiences and operational efficiency. This research provides a comprehensive analysis of AI’s impact on digital shopping in Saudi Arabia, contributing to the growing body of knowledge on AI’s influence in the global e-commerce market..